Components of airport experience and their roles in eliciting passengers' satisfaction and behavioural intentions. (December 2020) - Batouei, Amir; Iranmanesh, Mohammad; Mustafa, Hasrina; Nikbin, Davoud; Ping, Teoh Ai
Abstract: In the current competitive environment, airport managers are under growing pressure to attract more passengers and airlines, through the creation of desirable Airport Experiences. This study particularly delves into this newly emerged concept "Airport Experience, by examining the effects of AE's components on travellers' satisfaction and consequently their intentions to revisit and to spread word-of-mouth. Components of airport experience were measured from sociological, psychological, and services marketing perspectives. Data were collected from 377 travellers and were analysed using partial least squares technique. The findings show that service fairness, servicescape, service encounter, and self-service technologies have significant effects on travellers' satisfaction. Further, travellers' satisfaction is associated with their revisit intention and word of mouth. The findings of this study contribute to the literature by testing the impacts of sociological, psychological, and service marketing dimensions on travellers' satisfaction in one holistic model. The findings enable airport managers and marketers to develop effective strategies for increasing passengers' satisfaction, intentions to revisit, and spread positive word of mouth based on in-depth understating of the most influential airport experience elements.